Effect of Different Heparin Volumes on Blood Gas Analysis - Gholami, Narges; Pournasiri, Zahra; Mehregan, Fatemeh Fereshteh; Hatami, Hamidreza (Journal of Pediatric Nephrology, 2019)
Abstract Background and Aim: Blood gas analysis is an important laboratory test for diagnosis and treatment of a variety of medical conditions in emergency rooms. Inaccurate sample collection is one of the reasons for errors in blood gas analysis. This study was conducted to evaluate different volumes of heparin in syringes and the effect of sample dilution on blood gas analysis as one of the main factors affecting the results of blood gas analysis. Methods: One hundred children (4 months to 12 years) who presented to Loghman Hakim Hospital, Tehran, Iran, were enrolled in this study. Two samples were taken from each patient. For the first sample, the syringes were filled with heparin sodium and then emptied completely to achieve a very thin layer anticoagulant coating. For the second sample, the syringes were filled with 0.1 mL of liquid heparin sodium 5000 U/mL (5%). The blood gas parameters including pH, PO2, PCO2, HCO3 and BE (base excess) were measured. Data were analyzed using SPSS version 18. Results: All parameter had lower levels in second samples (0.1 mL heparin 5%) except for PO2 compared to the first samples (P < 0.001). Conclusion: This study found that a small amount of heparin in the syringe changed the result of blood gas analysis. Keywords: Blood Gas Analysis; Heparin; pH; PCO2; HCO3.